Perception Analysis Of Women Of Reliable Age In The Utilization Of Acetic Acid Visual Inspection In The Province Of Southeast Sulawesi - Sri Dinengsih; Juita Lesmana; Jenny Anna Siauta (Universitas Islam Lamongan, 2021)
Cervical cancer is an important health problem for women all over the world. Currently, the coverage of early detection of cervical cancer in Indonesia through IVA examinations is still very low, which is around 5%. Based on the results of a preliminary study, it was found that only 40% of women knew about cervical cancer in the Kombikuno Health Center Work Area in 2020. This study aims to determine the analysis of perceptions of female prostitutes in the use of IVA examinations at the Kombikuno Community Health Center. This study used a cross sectional research design. The number of samples in this study were 100 respondents. The data analysis used is by using the Chi square test. There is a significant relationship between knowledge, information sources and family support with the perception of female prostitutes in the use of IVA examinations at the Kombikuno Public Health Center, Muna Barat Regency, Southeast Sulawesi Province with the results of Value (0.000 ), (0.000) and (0.008). There is no significant relationship between the affordability of the distance and the perception of WUS in the IVA examination with Value (0.132). There is a significant relationship between knowledge, information sources and family support and perceptions of female prostitutes in the use of IVA examinations Suggestion: It is hoped that it can increase provision for cadres about early detection of cervical cancer, and involve health cadres to conduct counseling about cervical cancer in villages.